(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
A field experiment was conducted for two consecutive seasons(2014 and 2015), at the White Nile Research Farm, Kosti, White NileState, Sudan, to determine the seed rate for aerobic rice (Oryza sativa L.).The variety Kosti1 was sown directly on flat dry soil with varying seedrates: 40, 60, 80 and 100 kg/ha. The experiment was arranged in arandomized complete block design with three replications, in the twoseasons. The land was pre-irrigated and then disc harrowed and leveled.The crop was planted during the first week of July in both seasons.Characters studied were, Phenology, yield, biological yield and yieldcomponents. The combined and single analyses of variance for bothseasons showed that seed rate treatments exhibited highly significantdifferences in grain yield and yield components. The results showed that,increasing seed rate significantly increased number of panicles/ m2, thepercentage of empty grains, plant height, grain yield and biological yield.However, increasing seed rate reduced days to 50% flowering, the filledgrains and the 1000- grain weight. The results indicated that the seed rate(80 kg/ha) significantly increased the number of panicles/m2, biologicalyield and grain yield (kg/ha). The lowest and the highest yields/ha wereobtained at the seed rates of 40 and 80 kg/ha, respectively. The resultsindicated that, increasing seed rate from 40 to 60 kg/ha increased grainyield by 10 % and 16 % in the first and second seasons, respectively; andthat grain yield could be improved significantly in the two seasons by 6 %and 18 % by increasing seed rate from 60 to 80 kg/ha. However,increasing seed rate from 80 to 100 kg/ha reduced the grain yield by 17 %and 23 % in the first and second seasons, respectively. The highestmarginal rate of return (MRR) 1496 % was obtained from the 80 kg/haseed rate. Therefore, it is concluded that the optimum seed rate under theconditions of the present investigation was 80 kg/ha.